Nursing consultation to the user with hypertension in primary attention - Gilvan Ferreira Felipe; Thereza Maria Magalhães Moreira; Lúcia de Fátima da Silva; Andressa Suelly Saturnino de Oliveira (Rev Rene)
In primary care, the nursing care for hypertensive patients can be provided during the nursing consultation. The main aim of this research was to examine the activities developed by nurses during the nursing consultation for hypertensive patients followed in primary care. This descriptive study, developed in three Family Health Centers of the Regional IV Executive Secretary in Fortaleza, through monitoring of 39 consultations and completion of a checklist. It was found out that the consultations approached, more frequently, the identification of previous treatment of hypertension (100.0%), hypertensive drug intake (61.5%), investigation of modifiable cardiovascular risk factors (53.8 %), observation of the appearance of the user (100.0%), blood pressure monitoring (100.0%) and implementation of nursing care (87.2%), with emphasis on health education. Nevertheless, it was concluded that some important aspects are not being approached during the consultation, which can cause poor service to users with hypertension.